Expanding the reach and benefits of digital agriculture - Hambly Odame, Helen; Okello, Dorothy (Technical Centre for Agricultural and Rural Cooperation, 2019)
The Gender, Agriculture and Rural Development in the Information Society initiative was established in 2002 to support projects aimed at leveraging ICTs to enhance farmer knowledge and productivity. But did the programme help to close the gender and urban-rural gap in ICT access? Or is there a need for the scheme to be rolled out again?